LOW LEVELS OF MICROVESSEL DENSITY AND IMMUNOHISTOCHEMICAL EXPRESSION OF VASCULAR ENDOTHELIAL GROWTH FACTOR IN CARCINOGEN-INDUCED DUCTAL MAMMARY GLAND CARCINOMA OF RATS SUPPLEMENTED WITH GARLIC - Alsalih Hussein, Hutheyfa; Hamzah, Hazilawati; Shari, Mohd Rosly; Sabri, Jasni; Mustapha, Noordin Mohamed; Sithambaram, Shanmugavelu (Asian Journal of Pharmaceutical and Clinical Research, 2016)
The present study was conducted to evaluate the anti-angiogenesis activity of diet containing 5% of garlic powder (G) on mammary gland carcinoma induced by N-methyl-N-nitorsourea (MNU) in female Sprague Dawley rats. A total of 24 female Sprague Dawley rats were randomly assigned in to three groups namely, control, MNU and MNU+G (n=8). MNU group rats received four consecutive subcutaneous (sc) injections of MNU at a dose of 60 mg/kg per injection and basal diet, MNU+G group rats received four consecutive sc injections of MNU at a dose of 60 mg/kg per injection and diet containing 5% of garlic powder, while control rats were injected with normal saline and fed with normal diet. All rats were euthanised at 24 weeks of experimental period. Microvessel density (MVD) and vascular endothelial growth factor (VEGF) expressions were investigated through histopathology and immunohistochemistry methods. Results showed MNU induced ductal mammary gland carcinoma in rats of MNU and MNU+G groups. MVD scoring values showed significant (p<0.05) higher score of MNU group compared to MNU+G and control groups. Overexpression of VEGF was observed significantly (p<0.05) in MNU group compared to MNU+G and control groups. Administration of diet containing 5% of garlic powder to female Sprague Dawley rats minimised the development of ductal mammary gland carcinoma by inhibiting the angiogenesis activity.Â 